FARMERS INTELLECTUAL MOVEMENT THROUGH THE WARTANI ORGANIZATION OF CURAHNONGKO VILLAGE, JEMBER REGENCY - Hidayat, Nurul (Universitas Sebelas Maret (UNS), 2022)
The struggle of farmers in Curahnongko Village, Jember Regency to get their rights to land has gone through various dynamics. The conflict involving farmers and PTPN XII Kalisanen has been started since 1966. The conflict was triggered by land grabbing by PTPN Kalisanen at that time. Farmers who have long managed the land to be used as agricultural media feel lost, so that in the following years there were protests to claim their land. Peasants' protests increased with the fall of the New Order government in 1998. That year was a turning point for farmers to speak openly again for the return of their land. The waves of protests that never cease to provoke intellectuals to join in the arena of struggle. The intellectual actor then formed an organization to be used as a forum to accommodate farmers' concerns and fight for it together. The forum or organization is called WARTANI (Wadah Aspirasi Warga Tani). This study uses a qualitative method of ethnographic type. The data collection carried out in this study used three components, observation, interviews and documentation. The results of this study are divided into three, namely, 1) WARTANI plays an important role in the arena of conflict that occurs with PTPN. 2) the role of intellectuals has increased the knowledge of farmers and their mentality in the struggle for land rights. 3) the role of intellectuals in helping organizations in political networking with the government.